Prevalence of infection with high-risk HPV in women using hybrid capture conducting prevention of cervical cancer in Southern Brazil - Bicca, Guilherme Lucas de Oliveira; Silveira, Mariângela Freitas da; Silva, Suele Manjourany; Silva, Kleber Roberto Siguel da; Barros, Fernando Celso Lopes Fernandes de (Brazilian Journal of Sexually Transmitted Diseases, 2013)
Introduction: High-risk Human Papillomavirus (HR HPV) infection is known to be linked to cervical cancer, with molecular biology tests being an important tool in diagnosis. Objective: This study is aimed to quantify the prevalence of HPV infection in women from the Southern part of the State of Rio Grande do Sul, Brazil, correlating factors associated with the development of precursor lesions and of cervical cancer. Methods: 643 women were enrolled in the study, by filling out a standardized questionnaire and undergoing cytology, colposcopy, and HR HPV Hybrid Capture 2 (HC2) tests. Results: Most patients were aged between 20 to 39 years (70.6%), this decreased the percentage of smokers from 23% to 11%. The average age of sexual debut through the period studied was of 18 years old. HR HPV prevalence was correlated with younger ages, with fewer patients infected by HR HPV when they were older at first sexual activity. Almost 70% prevalence of infection was observed in women who had 4 or more sexual partners. Altered cytology and colposcopy results had significantly higher rates of HR HPV infection. 334 women were referred for biopsy. Of those, 321 had altered colposcopy results and cytopathology of ASC-US/AGC-US, LSILs and HSILs, with 231 biopsies performed by the study. None of the results indicated cervical cancer. HC2 showed higher specificity than cytology, with high positive and negative prediction values (49.8% and 78.6%, respectively).Conclusion: The inclusion of HR HPV testing in screening programs in Brazil, according to international policies, will lead to fewer biopsies in women without infection and increased interval between screenings.